Advances in pseudocapacitive and battery-like electrode materials for high performance supercapacitors. Issue 25 (16th June 2022) - Sahoo, Sumanta; Kumar, Rajesh; Joanni, Ednan; Singh, Rajesh Kumar; Shim, Jae-Jin
Abstract : Systematic survey on the fabrication and electrochemical performance of the most promising classes of pseudocapacitive/battery-type electrode materials for supercapacitors. Abstract : Supercapacitors are energy storage devices with unique characteristics, and together with batteries have generated a significant research effort, with various types of electrode materials having been developed over the last few years. Current trends for this application have been gradually shifting towards pseudocapacitive/battery-like materials. When compared to electric double-layer capacitors, pseudocapacitive/battery-type materials have a decisive advantage, since they are usually able to deliver improved energy density. Furthermore, these materials can undergo reversible electrochemical reactions within a very short period of time without compromising their high charge storage capacity. In this article, we systematically survey the current state of the art regarding the fabrication and electrochemical performance of the most promising classes of pseudocapacitive/battery-type electrode materials for supercapacitors. The text covers metal oxides, mixed metal oxides, conducting polymers, and MXenes. Closing the article, some of the outstanding problems for increasing the performance of SCs are discussed, and future research directions are suggested.